Some microbiological and chemical characteristics of fresh siirk, a traditional dairy product consumed in hatay, turkey - Abdullah Keleş; Osman Aygün; Mustafa Ardıç (Eurasian Journal of Veterinary Sciences)
In this study, randomly selected fifty samples of süık (çökelek) produced and consumed in Hatay (Turkey) region were investigated for both microbiological and chemical characteristics. The numbers of the microorganisms in the samples analysed were found as following: Total mesophilic bacteria 1,58x107 cfu/g, yeast and mould 8.17x105 cfu/g, lactic acid bacteria 8.31x106 cfu/g and Staphylococcus spp. 5.80x1 CP cfu/g. The mean values ol dry matter, fat, salt, ash, acidity as lactic acid and pH in sürk samples were found as 48.80%, 4.05%, 5.59%, 5.80%, 0.78% and 4.55, respectively.